Griya Boedaya: komoditas wahana berliterasi budaya sebagai wujud pengenalan budaya lokal di Jawa Timur - Iffa Maisyaroh; Silvi Oktavia (Universitas Padjadjaran, 2019)
The existing knowledge in society has not been spread explicitly. Thus local knowledge is still unknown to the people in the region itself. This study aimed to provide information related to the dissemination of local knowledge applied to cultural literacy programs form: ideas, behavior, and artifacts or works. The kind of the idea is stated in a paper, the behavior is shown in community activities, and artifacts are contained in works in the form of objects as results of activities and actions. The main focus is on basic human needs: clothing and food applied through Griya Boedaya tour. Clothing consists of typical East Javanese fabrics, while food consists of East Javanese specialties. The culture produced reflects the characteristics of the environment. Thus it has features standing out that becomes the identity of the local community’s culture. In the East Java region, knowledge is an invisible or intangible local asset owned by people in the area. This study used the literature method with qualitative approach by searching for books, e-journals, proceedings, thesis and articles. Results of the people’s knowledge in the form of typical food and unique clothing were a manifestation of people's expression of their environment. Griya Boedaya introduces local cultures such as regional cloth and cuisine and is a tourist means which introduces history, creation process, work systems, tools used, and the use and philosophy of local cultural products. Hopefully, the cultural literacy tour will enable people to recognize, know, and understand their culture with easy-to-understand and fun methods.